qSCMS: post-quantum security credential management system for vehicular communications. - Oliveira, Jefferson Evandi Ricardini Fernandes de (2019)
With the increasing demand for intelligent transportation systems (ITS), security and privacy requirements are paramount. This demand led to many proposals aimed at creating a Vehicular Public Key Infrastructure (VPKI) able to address such prerequisites. Among them, the Security Credential Management System (SCMS) is particularly promising, providing data authentication in a privacy-preserving manner and supporting the revocation of misbehaving vehicles. Namely, one of the main benefits of SCMS is its so-called butterfly key expansion process, which issues arbitrarily large batches of pseudonym certificates through a single request. Despite SCMS\'s appealing design, in this document, we show that its certificate issuing process can be improved. Namely, this protocol originally requires the vehicle to provide two separate public/private key pairs to registration authorities; we now propose an improved approach that unifies them into a single key pair. We also show that such performance gains come with no negative impact in terms of security, flexibility or scalability when compared to the original SCMS. Besides the improvement on the initial Elliptic Curve based protocol, we present a post-quantum version of the protocol using Ring Learning-with-errors (R-LWE) assumption. This new protocol has the same shape and features of the original one, but using R-LWE-based signature and encryption as underlying schemes and Lattices operation for the key issuing instead of Elliptic Curves.